O6-methylguanine inhibits the binding of transcription factors to DNA. - Bonfanti, M (1991)
To study the effect of methylation of O6-guanine on the binding of cellular factors to different DNA sequences, modified oligonucleotides were constructed, in which O6-Methylguanine (O6-MeG) replaced some guanines. The DNA sequences utilized were: the region of the c-fos promoter containing the binding site for serum response factor (SRF); the region of the HIV LTR containing two binding sites for the transcription factor NF kappa B; the region of the HIV LTR containing three binding sites for the cellular factor sp1. After incubation of labeled oligonucleotides, either unmodified or containing O6-MeG, with nuclear extracts obtained from different cell lines, gel retardation assays indicated that the presence of O6-MeG resulted in inhibition of binding of cellular factors to DNA sequences located in the promoter regions of genes. This inhibition was not the same for all modified oligonucleotides but dependent on the position in which O6-MeG was located. The results obtained indicate that alkylation of O6-guanine affects the binding of transcription factors and thereby possibly the regulation of genes expression.